2019
DOI: 10.1038/s41419-019-1527-z
|View full text |Cite
|
Sign up to set email alerts
|

Srlp is crucial for the self-renewal and differentiation of germline stem cells via RpL6 signals in Drosophila testes

Abstract: Self-renewal and differentiation in germline stem cells (GSCs) are tightly regulated by the stem cell niche and via multiple approaches. In our previous study, we screened the novel GSC regulatory gene Srlp in Drosophila testes. However, the underlying mechanistic links between Srlp and the stem cell niche remain largely undetermined. Here, using genetic manipulation of the Drosophila model, we systematically analyze the function and mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…20,21 And ribosomal subunits could act as an intermediary to affect GSC self-renewal and differentiation in the Drosophila testis. 22 We showed that both RpS13 and Rho1 could regulate the expression of ribosome subunits. Consequently, it is highly possible that Therefore, these results indicate that RpS13, together with the small GTPase Rho1, are crucial for GSC self-renewal and differentiation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…20,21 And ribosomal subunits could act as an intermediary to affect GSC self-renewal and differentiation in the Drosophila testis. 22 We showed that both RpS13 and Rho1 could regulate the expression of ribosome subunits. Consequently, it is highly possible that Therefore, these results indicate that RpS13, together with the small GTPase Rho1, are crucial for GSC self-renewal and differentiation.…”
Section: Discussionmentioning
confidence: 89%
“…Immunofluorescence assays were carried out as described previously. 22 Testes were dissected in 1 × PBS and fixed for 30 minutes in 4% paraformaldehyde (PFA), then washed 3 times with 0.3% PBS-Triton X-100 (PBST) and blocked for 1 hour in 5% bovine serum albumin (BSA) (Sangon Biotech, Shanghai, China). Next, the testes were incubated overnight at 4°C with primary antibodies (Table S3) diluted in 5% BSA.…”
Section: Immunofluorescencementioning
confidence: 99%
“…S2 cells were collected after transfection for 48 h. Cell apoptosis was determined using the TUNEL assay according to the manufacturer’s protocols 37 . The TUNEL BrightRed Apoptosis Detection Kit was obtained from Vazyme (A113, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…S2 cells were collected after transfection for 48 h. Flow cytometry was performed using an Annexin V/PI Apoptosis Assay Kit (FMSAV647-100, FcMACS, Nanjing, China) 37 . After transfection for 48 h, S2 cells were washed with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Raw data for each replicate is shown in Table S2. In each case, we retained target proteins that were identified in every replicate experiment with the given bait protein (n=5 in each case), but which and were absent from all controls (45). The primary screen revealed a list of 63 proteins that we subdivided into two main groups, nuclear (Table 4) and mitochondrial candidates ( Table 5), based on the major subcellular location of the protein as currently annotated in Flybase (www.flybase.org).…”
Section: Protein Interactors With Rnase H1mentioning
confidence: 99%